Five-Aminosalicylic Acid: An Update for the Reappraisal of an Old Drug - Cristiana Perrotta; Paolo Pellegrino; Eliana Moroni; Clara De Palma; Davide Cervia; Piergiorgio Danelli; Emilio Clementi (Gastroenterology Research and Practice)
Inflammatory bowel disease (IBD) comprises several conditions with chronic or recurring immune response and inflammation of the gastrointestinal apparatus, of which ulcerative colitis and Crohn’s disease are the commonest forms. This disease has a significant prevalence and it is of an unknown aethiology. Five-aminosalicylic acid (5-ASA) and its derivatives are among the oldest drugs approved for the treatment of the IBD. In this review we reapprise aspects of 5-ASA mechanism of action, safety, and efficacy that in our opinion make it a valuable drug that can be fruitfully tailored in personalised treatments as a therapeutic option alongside other immune-modifying agents.